2016
DOI: 10.3329/bjo.v21i2.27645
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study on Hypopharyngeal Carcinoma in Dhaka Medical College Hospital

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This finding almost agrees with that of Islam et al who found that moderate differentiation accounted for 50% of all differentiation. 14 The majority of patients' sub-sites (81.4%) were pyriform sinuses. According to Aich et al pyriform fossa accounts for 80% of cases of hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This finding almost agrees with that of Islam et al who found that moderate differentiation accounted for 50% of all differentiation. 14 The majority of patients' sub-sites (81.4%) were pyriform sinuses. According to Aich et al pyriform fossa accounts for 80% of cases of hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 94%
“…11 The vast majority of people with head and neck cancer are detected at a late stage. 14 A total of 172 patients were studied for this study in order to assess the epidemiological and clinicopathological features of hypopharyngeal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations